Small isomeric push-pull chromophores based on thienothiophenes with tunable optical (non)linearities - Podlesný, Jan; Pytela, Oldřich; Klikar, Milan; Jelínková, Veronika; Kityk, Iwan V.; Ozga, Katarzyna; Jedryka, Jaroslaw; Rudysh, Myron; Bureš, Filip (Royal Society of Chemistry, 2019)
Fourteen new D-pi-A push-pull chromophores based on two isomeric thienothiophene donors and seven acceptors of various electronic natures have been designed and conveniently synthesized. In contrast to known thienothiophene push-pull molecules, the prepared small chromophores proved to be organic materials with easily tunable thermal, electrochemical and (non)linear optical properties. It has also been shown that small structural variation may result in significantly improved/varied fundamental properties. Very detailed structure-property relationships were elucidated within the systematically developed series of push-pull molecules, which may serve as a useful guide in designing new D-pi-A molecules based on fused thiophene scaffolds.
Malé isomerní push-pull chromofory na bázi thienothiofenu s možností ladění (ne)linearit
Keywords: electron-donors; small-molecule; high-mobility; side-chain; pi-linkers; performance; emission; crystals; acceptor; polymer; elektrondonory; malé molekuly; emise; krystaly; akceptor; polymer